Role of rare‐earth Y addition on formation and anticorrosion properties of MAO coating on 2024 aviation aluminum alloy. Issue 1 (27th October 2022) - Zhang, Defen; Ran, Yun; Chen, Xiaowen; Xia, Jun; Cai, Liping; Ping, Wei
Abstract: Different ceramic coatings were prepared on the surface of 2024 aviation aluminum alloy using micro‐arc oxidation process in silicate based electrolyte combined with the rare earth based compound Y(NO3 )3 ·6H2 O. The thickness, hardness of the coating and conductivity of electrolyte were tested using relative devices, morphology and chemical composition were studied by scanning electron microscope and energy dispersive spectroscope, respectively. The phase composition of the coatings was characterized by X‐ray diffraction and X‐ray photoelectron spectroscopy. Furthermore, the corrosion resistance of the coating was evaluated by an electrochemical workstation. The results showed that the addition of Y(NO3 )3 ·6H2 O could improve the thickness and hardness of the coating. The morphological observation of the coating showed that Y(NO3 )3 ·6H2 O was successfully incorporated into the ceramic layer and that the coating had the smallest porosity at 1.5 g/L Y(NO3 )3 . The phase composition of the coating was mainly γ‐Al2 O3, α‐Al2 O3, SiO2, Y2 O3, and AlPO4 . The corrosion resistance of coating in simulated seawater with the addition of Y(NO3 )3 ·6H2 O was significantly improved, and the values of | Z |0.01 Hz and corrosion rate of the coating reached the maximum and minimum at 1.5 g/L Y(NO3 )3, which were 5.63 × 10 5 Ω cm 2 and 7.444 × 10 −4 mm/a, respectively.